2005
DOI: 10.1177/097265270400400105
|View full text |Cite
|
Sign up to set email alerts
|

Size Anomaly on the Taiwan Stock Exchange

Abstract: This study uses the stochastic dominance theory, which is distribution-free, to examine the relationship between realised returns and firm size for companies listed on the Taiwan Stock Exchange between 1982 and 1999. The findings show that small-cap and large-cap portfolios outperform both medium-cap portfolios and the market, when investors are allowed to borrow and lend money at prevailing risk-free rates. The ‘traditional’ size effect exists only when investors are permitted to borrow and lend money at very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Considering the evidence in the literature that traditional systematic risk factors like the market or size effect does not necessarily apply to this emerging market (e.g. Chui and Wei, 1998;Liao, 2005;Cakici et al, 2013Cakici et al, , 2016, we conclude that the profits reported in Tables IV and V are not necessarily driven by (or associated with) certain systematic risk factors and that herding indeed is the primary driver of profitability in our results [4].…”
Section: Herding-based Investment Strategiesmentioning
confidence: 59%
“…Considering the evidence in the literature that traditional systematic risk factors like the market or size effect does not necessarily apply to this emerging market (e.g. Chui and Wei, 1998;Liao, 2005;Cakici et al, 2013Cakici et al, , 2016, we conclude that the profits reported in Tables IV and V are not necessarily driven by (or associated with) certain systematic risk factors and that herding indeed is the primary driver of profitability in our results [4].…”
Section: Herding-based Investment Strategiesmentioning
confidence: 59%
“…Finally, another justification for using these portfolios is provided by Liao (2005) who shows that small cap and large cap portfolios outperform both medium cap portfolios and the market. Table 1 reports descriptive statistics for small and large cap return series for the period 3 January 1990 to 5 January 2005.…”
Section: Datamentioning
confidence: 98%